Structure of the murine Jak2 protein-tyrosine kinase and its role in interleukin 3 signal transduction. - Silvennoinen, O (1993)
Interleukin 3 (IL-3) regulates the proliferation and differentiation of hematopoietic cells. Although the IL-3 receptor chains lack kinase catalytic domains, IL-3 induces tyrosine phosphorylation of cellular proteins. To investigate the potential role of the JAK family of protein-tyrosine kinases in IL-3 signal transduction, we have obtained full-length cDNA clones for murine Jak1 and Jak2 protein-tyrosine kinases and prepared antiserum against the predicted proteins. Using antisera against Jak2, we demonstrate that IL-3 stimulation results in the rapid and specific tyrosine phosphorylation of Jak2 and activates its in vitro kinase activity.